Comparison of outcomes of surgeon-performed intraoperative ultrasonography-guided wire localization and preoperative wire localization in nonpalpable breast cancer patients undergoing breast-conserving surgery: A retrospective cohort study. Issue 50 (December 2017) - Shin, Young Duck; Choi, Young Jin; Kim, Dae Hoon; Park, Sung Su; Choi, Hanlim; Kim, Dong Ju; Park, Sungmin; Yun, Hyo Yung; Song, Young Jin
Abstract : Abstract: This study aimed to determine the efficacy of intraoperative ultrasonography-guided wire localization guided breast-conserving surgery (BCS) for nonpalpable breast cancer and compare it to conventional preoperative wire localization (PWL) guided surgery. We retrospectively analyzed the medical charts of 214 consecutive nonpalpable breast cancer patients who underwent BCS using intraoperative ultrasonography-guided wire localization by a surgeon (IUWLS) and PWL, between April 2013 and March 2017. Positive surgical margins, reexcision rates, and resection volumes were investigated. Of the total cohort, 124 patients underwent BCS with IUWLS and 90 patients with PWL. The following did not differ between the IUWLS and PWL groups: positive margin status, re-excision rate, conversion rate, permanent positive margin status, reoperation rate, median optimal resection volume (ORV), median total resection volume (TRV), and median closest tumor-free margin. Rather, median (range) widest tumor-free margin was significantly smaller in the IUWLS group (9 mm [5–12]) than in the PWL group (14 mm [9–20]; P  = .003]). Median (range) calculated resection ratio (CRR) was significantly lower in the IUWLS group (1.67 [0.87–9.38]) than in the PWL group (4.83 [1.63–21.04]; P  = .02). In nonpalpable breast cancer patients undergoing BCS, IUWLS showed positive resection margins and reexcision rates equivalent to those of the conventional PWL method. Additionally, excision volume and widest tumor-free margin were smaller with IUWLS, confirming that healthy breast tissue is less likely to be resected with this method. Our results suggest that IUWLS offers an excellent alternative to PWL, while avoiding PWL-induced patient discomfort.